2015
DOI: 10.1158/1078-0432.ccr-15-1243
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Biological Activity of Imatinib in Metastatic Dermatofibrosarcoma Protuberans (DFSP)

Abstract: Purpose: To report on imatinib mesylate (IM) in patients with metastatic dermatofibrosarcoma protuberans (DFSP)/fibrosarcomatous (FS)-DFSP and on the impact of the treatment on tumor biology.Experimental design: Ten consecutive patients treated with IM from 2007 to 2015 for a metastatic relapse from DFSP/FS-DFSP were identified. FISH analysis for COL1A1-PDGFB was performed. Two IM-treated and 4 na€ ve FS-DFSP were transcriptionally profiled by RNAseq on HiScanSQ platform. Differential gene expression was analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 37 publications
(55 reference statements)
3
56
2
Order By: Relevance
“…To this end, we initially compared the transcriptome profile of 5 DFSPs and of 5 FS-DFSPs. All samples expressed the COL1A1-PDGFB fusion transcript, with no significant variation in its expression levels between DFSP and FS-DFSP, as previously reported (4,8). No other recurrent fusion transcripts that may hallmark the FS-DFSP variant were detected.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…To this end, we initially compared the transcriptome profile of 5 DFSPs and of 5 FS-DFSPs. All samples expressed the COL1A1-PDGFB fusion transcript, with no significant variation in its expression levels between DFSP and FS-DFSP, as previously reported (4,8). No other recurrent fusion transcripts that may hallmark the FS-DFSP variant were detected.…”
Section: Discussionsupporting
confidence: 77%
“…Cases of fibrosarcomatous transformation occurring over time in DFSP after multiple local relapses are described in other reports (8). We cannot challenge this possibility, as the proportion of patients who relapsed was very low.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Scarce data exists on the role of imatinib specifically in these metastatic FS-DFSP tumors. A recent retrospective study evaluating 10 metastatic FS-DFSP patients treated with imatinib showed that 90% of patients achieved clinical benefit (8 partial responses and 1 stable disease) with a median of 11 months PFS [87]. However, the duration of response observed in this study was lower than that reported ina previous series containing a mix of cases with both low-grade and FS-DFSP [88].…”
Section: Targeted Therapycontrasting
confidence: 53%
“…Imatinib mesylate is also used in metastatic tumors in which resection is not possible or may have unacceptable functional and cosmetic results and radiotherapy cannot be performed. [12][13][14] This study aimed to review the literature for DFSP cases.…”
Section: Introductionmentioning
confidence: 99%